2007
DOI: 10.1021/pr070063h
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Studies of Human Hepatocellular Carcinoma Using High-Resolution Magic-Angle Spinning 1H NMR Spectroscopy in Conjunction with Multivariate Data Analysis

Abstract: High-resolution magic-angle spinning (MAS) 1H nuclear magnetic resonance spectroscopy has been employed to characterize the metabolite composition (i.e., metabonome) of the human hepatocellular carcinoma (HCC) tumor in combination with principal component analysis (PCA). The results showed that (a) the metabonomes of both low-grade HCC and high-grade HCC tumors differ markedly from that of the adjacent non-involved tissues; and (b) low-grade HCC tumors have clear differences in metabonome from that of the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
202
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(237 citation statements)
references
References 44 publications
34
202
0
1
Order By: Relevance
“…It has been reported that cancer cells predominantly produce energy by glycolysis rather than oxidative phosphorylation via the tricarboxylic acid (tCA) cycle (38). promotion of glycolysis and disruption of the tCA cycle were also noted in invasive ovarian carcinoma (32), liver cancer (39) and colorectal cancer (40). Abnormal metabolism of carbohydrates may be associated with tumor growth with a large energy requirement needed for aggressive cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cancer cells predominantly produce energy by glycolysis rather than oxidative phosphorylation via the tricarboxylic acid (tCA) cycle (38). promotion of glycolysis and disruption of the tCA cycle were also noted in invasive ovarian carcinoma (32), liver cancer (39) and colorectal cancer (40). Abnormal metabolism of carbohydrates may be associated with tumor growth with a large energy requirement needed for aggressive cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glutamine synthetase expression is correlated with HCC progression [93,96]. Supporting the importance of glutamine metabolism in liver cancer, increased concentrations of glutamate and glutamine have been detected in human HCC in comparison to adjacent normal tissue [97]. Interestingly, glutamine synthethase expression is related to liver regeneration and therefore is observed during cirrhosis (a pre-state of liver cancer) [93,98].…”
Section: Metabolic Alterations In Liver Cancermentioning
confidence: 93%
“…Five metabolites quinaldic acid, β-sitosterol, arachidyl carnitine, oleamide and tetradecanal were observed for the first time. Nine metabolite lysophosphatidylethanolamines, glycerophosphocholine, LPCs, CDCA glycine conjugate and Lphenylalanine had been reported as serum metabolite biomarkers for HCC diagnosis in previous research [39][40][41].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 99%